PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA DI SMP NEGERI 51 SURABAYA - AFIDAH, NURUL; SUDIBYO, ELOK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Students' science literacy skills are one of the foundations in developing the competencies and character quality demanded in 21st-century learning, so it is important for teachers to help students improve their science literacy skills by applying appropriate teaching strategies. This study aims to describe students' science literacy skills after participating in learning by applying the guided inquiry model on the topic of Global Warming in the 9th grade at SMP Negeri 51 Surabaya. The one group pretest-posttest design was used with 29 students from class IX C as the research subjects. Research data were collected through a testing method adjusted to the science literacy indicators in the science competency aspect. Data analysis used a dependent sample t-test and N-gain analysis. The research results show a significant improvement in students' science literacy skills, indicated by a sig. (2-tailed) value of 0.000 < 0.05. This means that H1 is accepted and H0 is rejected, so it can be stated that there is a difference in the average science literacy skills of students before and after the implementation of the guided inquiry model. Additionally, the N-gain analysis shows an average score of 0.75, which falls into the high category. Based on the research results, it can be concluded that the guided inquiry model is capable of improving students' science literacy skills in the aspect of science competence. ABSTRAKKemampuan literasi sains siswa menjadi salah satu pondasi dalam mengembangkan kompetensi dan kualitas karakter yang dituntut pada pembelajaran abad ke-21, sehingga penting bagi guru untuk membantu siswa meningkatkan kemampuan literasi sains dengan menerapkan strategi pembelajaran yang tepat. Penelitian ini bertujuan untuk mendeskripsikan kemampuan literasi sains siswa setelah mengikuti pembelajaran dengan menerapkan model inkuiri terbimbing pada materi Pemanasan Global di kelas IX SMP Negeri 51 Surabaya. Desain one group pretest-posttest digunakan dengan menjadikan sejumlah 29 siswa kelas IX C sebagai subjek penelitian. Data penelitian dikumpulkan melalui metode tes yang disesuaikan dengan indikator literasi sains pada aspek kompetensi sains. Analisis data mempergunakan dependent sample t-test dan analisis N-gain. Hasil penelitian menunjukkan adanya peningkatan kemampuan literasi sains siswa yang signifikan, ditunjukkan oleh nilai sig. (2-tailed) sebesar 0,000 < 0,05. Hal ini memiliki arti H1 diterima dan H0 ditolak, sehingga bisa dinyatakan ada perbedaan rata-rata kemampuan literasi sains siswa sebelum dan sesudah penerapan model inkuiri terbimbing. Selain itu, analisis N-gain menunjukkan skor rata-rata sejumlah 0,75 yang masuk dalam kategori tinggi. Berdasarkan hasil penelitian, bisa didapatkan kesimpulan yaitu model inkuiri terbimbing mampu meningkatkan kemampuan literasi sains siswa pada aspek kompetensi sains.